2020
DOI: 10.1001/jamapediatrics.2019.5104
|View full text |Cite
|
Sign up to set email alerts
|

Association of Maternal Exposure to Persistent Organic Pollutants in Early Pregnancy With Fetal Growth

Abstract: Prenatal exposure to persistent organic pollutants (POPs) has been associated with birth size, but data on fetal growth and among racially/ethnically diverse pregnant women remain scarce.OBJECTIVES To assess the association between maternal plasma POPs in early pregnancy and fetal growth and by infant sex and maternal race/ethnicity. DESIGN, SETTING, AND PARTICIPANTSThis cohort study used the National Institute of Child Health and Human Development Fetal Growth Studies-Singleton cohort, which recruited nonobes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(46 citation statements)
references
References 53 publications
2
42
1
1
Order By: Relevance
“…Previously, we found significant associations between maternal plasma concentrations of specific POPs and fetal growth and birth anthropometry measures [ 8 , 9 ]. To examine whether the change in methylation at the CpG sites significantly associated with POPs in the present analysis are related to neonatal anthropometry, we tested the correlations of methylation levels at each of the 214 CpG sites with neonatal anthropometry measures (birth weight, birth length, and head circumference).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we found significant associations between maternal plasma concentrations of specific POPs and fetal growth and birth anthropometry measures [ 8 , 9 ]. To examine whether the change in methylation at the CpG sites significantly associated with POPs in the present analysis are related to neonatal anthropometry, we tested the correlations of methylation levels at each of the 214 CpG sites with neonatal anthropometry measures (birth weight, birth length, and head circumference).…”
Section: Resultsmentioning
confidence: 99%
“…POPs are ubiquitous endocrine-disrupting compounds (EDC) that interfere with maternal hormones and can impact fetal development and health in later life. Studies have reported that maternal levels of POPs during pregnancy are associated with decrements in fetal growth and birth weight [ 5 9 ], neurodevelopmental disorders [ 10 ], earlier age of menarche [ 11 ], and genitourinary conditions in offspring [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fetal alcohol biomarkers and genetic research are believed to play a central role in determining the onset of FASDs, however, due to the nature of our dataset, we were unable to control for related variables. Considerably more research regarding this area is warranted 37 .…”
Section: Discussionmentioning
confidence: 99%
“…While evidence has been conflicting regarding the association between alcohol diagnosis prior to and during pregnancy and risk of adverse birth outcomes, one prospective cohort of 1303 pregnant women in the United Kingdom found that intakes of more than 2 units of alcohol/week before pregnancy, and in trimesters 1 and 2, were significantly associated with increased risk of babies with lower birth weight, lower birth centile, and preterm birth compared to non-drinkers [ 17 ]. Likewise, in a recent animal study in South Korea, alcohol consumption before or during pregnancy was associated with increased risk of abnormal fetal development in ethanol-fed mice, who not only had significantly decreased growth rates during the lactation period, but postnatal macrosomia [ 25 , 26 ]. Although these results were not replicated in our study, we also saw an inverse pattern between AUD diagnosis proximity to delivery and adverse birth outcomes.…”
Section: Discussionmentioning
confidence: 99%